High‐Speed NIR‐Driven Untethered 3D‐Printed Hydrogel Microrobots in High‐Viscosity Liquids. (18th January 2023) - Chen, Yin; Li, Mingliang; Tang, Qianqian; Cheng, Yifan; Miao, Anqi; Cheng, Liang; Zhu, Shilu; Luo, Tingting; Liu, Guangli; Zhang, Lijiu; Niu, Fuzhou; Zhao, Liang; et al.
Abstract : Untethered synthetic microrobots have significant potential to revolutionize biomedical interventions therapy in the future. However, the relatively slow speed of microrobots and viscosity biofluid environments are some of barriers standing in the way of microrobots' biomedical applications. Herein, inspired by high‐speed biological escape propulsion, NIR‐driven microrobots with a high‐speed, unidirectional propulsion in the high‐viscosity liquid are proposed. The bubble's growth and ejection cause the proposed 3D‐printed microrobot to propel forward. The 3D‐printed claw‐like microrobot achieves motion average speed of 1.4 mm s −1 (three‐body length (bl) s −1 ) when driven by NIR light in a pure glycerol viscous (945 mPa s, 25 °C) environment, which has a viscosity that is more than 200 times the viscosity of blood and of 54 mm s −1 (120 bl s −1 ) when driven by NIR light in deionized (DI) water. This work provides more ideas for the design and propulsion of light‐driven microrobots in a high‐viscosity vivo environment, which may broaden the applications of microrobots in the biomedical field, such as propulsion and navigation in confined and hard‐to‐reach body location areas. Abstract : A claw‐like asymmetric hydrogel microrobot undergoes ejection self‐propulsion upon NIR light irradiation at high speed. The "bomb‐like" behavior generates bubble streams under NIR light and drives the ejection propulsion of the microrobots. The microrobots also display efficient translational controllable propulsion in a high‐viscosity environment.